Are China's unit labour costs still competitive? A comparison with ASEAN countries. (5th March 2018) - Cui, Yuming; Lu, Changrong
Abstract : The rapidly rising wages and renminbi (RMB) revaluation have attracted lively debate about whether China can continue its rapid economic growth by relying on labour‐intensive goods exports. By comparing the competitiveness in labour costs between China and ASEAN countries, with a particular emphasis on unit labour costs, we find that China has lost its competitiveness in labour costs relative to ASEAN countries. However, our results show that some regions in China, such as the northeast and northwest, still have an advantage relative to ASEAN countries. Thus, China can duplicate Akamatsu's Flying Geese Paradigm by transferring labour‐intensive manufacturing industry from its coastal areas to non‐coastal areas.